A Novel Approach for Investigating Parkinson’s Disease Personality and Its Association With Clinical and Psychological Aspects - Carelli, Laura; Solca, Federica; Torre, Silvia; Pasquini, Jacopo; Morelli, Claudia; Pezzati, Rita; Mancini, Francesca; Ciammola, Andrea; Silani, Vincenzo; Poletti, Barbara (Frontiers in Psychology, 2019)
Objective: A complex relationship between neuropsychiatric symptoms, personality traits and neurochemical changes in patients with Parkinson’s Disease (PD) has been highlighted in the past several decades. In particular, a specific Parkinson personality with obsessive traits has been described. However, despite the great amount of anecdotal evidence, this aspect, together with its neurobiological, psychological and clinical correlates, are still not clearly defined. Therefore, we performed a case-control study in order to investigate the presence and rate of obsessive personality traits in PD patients within the theoretical framework of cognitive-constructivist model. Moreover, the relationship between PD personality and clinical, psychological and quality of life (QoL) aspects in PD were investigated. Methods: Fifty-one non-demented patients with probable or possible PD (not demented) were recruited at the inpatient-outpatient San Luca Hospital, IRCCS Istituto Auxologico Italiano. Control group was composed by forty-eight age- and education-matched healthy volunteers. Patients underwent a neurological investigation including Unified PD Rating Scale (UPDRS), Modified Hoehn & Yahr and Schwab & England staging scales. The following psychological questionnaires were administered to the overall sample: Personal Meaning Questionnaire (PMQ), State-Trate Anxiety Inventory – Form Y (STAI-Y), Beck Depression Inventory (BDI), Symptom Check List 90 (SCL-90), Short-Form Health Survey 36 (SF-36). Results: No significant differences in personality styles were observed in PD patients and controls, with a prevalence of phobic personal meaning organization (PMO) in both groups. However, PD patients showed more anxiety, depression and obsessive-compulsive symptoms than controls at the psychological questionnaires, as well as poorer QoL levels. The intensity of personality traits, and in particular for the obsessive personality style, were negatively associated with QoL and positively with disease severity. No significant relationships were observed between personality and other clinical aspects, such as side of onset and disease duration. Conclusion: PD patients did not show a different personality profile according to the cognitive-constructivist model with respect to controls. However, in this population, a general enhancement in the tendency to codify experience by means of specific cognitive and emotional patterns was associated to disease progression and to a poorer QoL.